Mesenchymal Stem Cell Exosomes Induce Proliferation and Migration of Normal and Chronic Wound Fibroblasts, and Enhance Angiogenesis In Vitro - Shabbir, Arsalan (Stem Cells Dev, 2015)
Although chronic wounds are common and continue to be a major cause of morbidity and mortality, treatments for these conditions are lacking and often ineffective. A large body of evidence exists demonstrating the therapeutic potential of mesenchymal stem cells (MSCs) for repair and regeneration of damaged tissue, including acceleration of cutaneous wound healing. However, the exact mechanisms of wound healing mediated by MSCs are unclear. In this study, we examined the role of MSC exosomes in wound healing. We found that MSC exosomes ranged from 30 to 100-nm in diameter and internalization of MSC exosomes resulted in a dose-dependent enhancement of proliferation and migration of fibroblasts derived from normal donors and chronic wound patients. Uptake of MSC exosomes by human umbilical vein endothelial cells also resulted in dose-dependent increases of tube formation by endothelial cells. MSC exosomes were found to activate several signaling pathways important in wound healing (Akt, ERK, and STAT3) and induce the expression of a number of growth factors [hepatocyte growth factor (HGF), insulin-like growth factor-1 (IGF1), nerve growth factor (NGF), and stromal-derived growth factor-1 (SDF1)]. These findings represent a promising opportunity to gain insight into how MSCs may mediate wound healing.